PENGARUH TANGGUNG JAWAB SOSIAL, PENGELOLAAN PENGETAHUAN DAN PENGELOLAAN SISTEM KERJA PEGAWAI TERHADAP KINERJA PEGAWAI DENGAN TATA KELOLA PERUSAHAANSEBAGAI VARIABEL INTERVENING - jurnalpps pps; Rizka Paramitha Servanda; Nugroho Mardi Wibowo (Prodi Magister Manajemen Universitas Wijaya Putra, 2021)
The purpose of this study was to determine the effect of social responsibility, knowledge management, management of employee work systems, corporate governance on employee performance in the field of medical supplies and equipment at RSUD Dr. Soetomo. The sample selection technique in this study was a census, namely all employees were taken as a sample of 45 employees. The data analysis technique used path analysis. The results of the study show that social responsibility has a significant effect on governance, knowledge management has a significant effect on governance, management of employee work systems has a significant effect on governance in the Medical Supplies and Equipment Sector of RSUD Dr. Soetomo. Employee social responsibility has a significant effect on employee performance, employee knowledge management has a significant effect on employee performance, employee knowledge management has a significant effect on employee performance in the Medical Supplies and Equipment Division of RSUD Dr. Soetomo. Employee governance has a significant effect on employee performance in the Medical Supplies and Equipment Division of RSUD Dr. Soetomo.